Comparative Transcriptome Analysis of Male Sterile Anthers Induced by High Temperature in Wheat (Triticum aestivum L.) - Liu, Hongzhan; Sun, Zhongke; Hu, Lizong; Li, Chaoqiong; Wang, Xueqin; Yue, Zonghao; Han, Yulin; Yang, Guangyu; Ma, Keshi; Yin, Guihong (Frontiers in Plant Science, 2021)
Global warming will have a negative effect on agricultural production as high temperature (HT) stress can seriously threaten plant growth and reproduction. Male sterility caused by HT may be exploited by the creation of a male-sterile line, which has great potential for application in crop heterosis. Therefore, it is important to understand the molecular mechanisms of anther abortion induced by HT in wheat, which remain unclear at present. In this study, we performed phenotype improve language in the abstract and comparative transcriptome analysis of the male sterile anthers induced by HT in wheat. Compared with Normal anthers, the cytological analysis indicated that HT-induced male sterile anthers were smaller and had no starch accumulation in pollen grains, which is consistent with the results observed by scanning electron microscopy (SEM). The 9601 differentially expressed genes (DEGs) identified by transcriptome sequencing compared with the Normal anthers were noticeably involved in the following pathways: starch and sucrose metabolism, phosphatidylinositol (PI) signaling system, peroxidase activity and response to oxidative stress, and heme binding. In addition, TUNEL assays were performed and the results further confirmed the excessive accumulation of reactive oxygen species (ROS) in sterile anthers. Moreover, a total of 38 hub genes were obtained from the protein-protein interaction network analysis of these pathways, including genes, for example, heat shock protein 90 (HSP90), thioredoxin-like protein 1, peroxidase (POD), calreticulin, UDP glucose pyrophosphorylase (UGPase), sucrose synthase, phosphatidylinositol-4-phosphate 5-Kinase (PIP5K), cytochrome c, and Cystathionine beta-synthase X6-like (CBSX6-like). These findings provide insights for predicting the functions of the candidate genes, and the comprehensive analysis of our results is helpful for studying the abortive interaction mechanism induced by HT in wheat.